Efektivitas E-LKPD Hidrokarbon Berbasis Problem Based Learning terhadap Hasil Belajar Peserta Didik Kelas X SMK SMTI Padang - Firnanda Aji Saputra; Syamsi Aini (MASALIQ, 2026)
Although the use of electronic Student Worksheets (e-LKPD) and the Problem Based Learning (PBL) model has been widely studied, research that specifically analyzes the effectiveness of PBL-based hydrocarbon e-LKPD that has been declared valid and practical on the learning outcomes of vocational high school students remains limited. This study aims to analyze the effectiveness of PBL-based hydrocarbon e-LKPD on the learning outcomes of Grade X students at SMK SMTI Padang. This study used a quantitative approach with a quasi-experimental nonequivalent control group design involving 70 students selected through purposive sampling. Data were collected using a multiple-choice test instrument administered through pretests and posttests, and then analyzed using descriptive statistics, prerequisite tests, N-Gain analysis, and Analysis of Covariance (ANCOVA). The results showed that the mean posttest score of the experimental class was 83.69, which was higher than that of the control class, which was 62.74. The experimental class obtained an N-Gain score of 0.76 in the high category, while the control class obtained an N-Gain score of 0.39 in the moderate category. The ANCOVA results showed that the use of PBL-based hydrocarbon e-LKPD had a significant effect on students’ learning outcomes after controlling for initial ability (F = 82.439; p < 0.001). These findings contribute to the development of technology-based chemistry learning and expand understanding of the effectiveness of digital learning media integrated with PBL in vocational education. The conclusion of this study affirms that PBL-based hydrocarbon e-LKPD is effective in improving students’ learning outcomes. The implications of this study include theoretical contributions to the development of digital chemistry learning literature and practical implications for teachers and schools in implementing interactive learning media that are relevant to vocational learning needs.